Renal Transporter‐Mediated Drug‐Drug Interactions: Are They Clinically Relevant?. (July 2016) - Lepist, Eve‐Irene; Ray, Adrian S.
Abstract: The kidney, through the distinct processes of passive glomerular filtration and active tubular secretion, plays an important role in the elimination of numerous endobiotics (eg, hormones, metabolites), toxins, nutrients, and drugs. Renal transport pathways mediating active tubular secretion and reabsorption in the proximal tubule are complex, involving apical and basolateral transporters acting in concert. Detailed studies of the molecular mechanisms of net active tubular secretion have established the involvement of multiple transporters with overlapping substrate specificity mediating competing secretion and reabsorption pathways. Although drug interactions arising from inhibition of renal transporters are rare relative to other mechanisms, they can involve commonly administered drugs (eg, cimetidine, metformin), may be underappreciated due to muted effects on plasma pharmacokinetics relative to tissue levels, can affect narrow‐therapeutic‐index medications (eg, antiarrhythmic, oncology medications), and may disproportionately affect sensitive populations where polypharmacy is common (eg, the elderly, diabetics). In particular, there is the potential for larger‐magnitude interactions in subjects with reduced glomerular filtration rates due to the increased relative contribution of tubular secretion. The assessment of additional endpoints in drug‐drug interaction studies including pharmacodynamics, positron emission tomography imaging, and metabolomics promises to expand our understanding of the clinical relevance of renal drug interactions.